Optimizing Cerebral Palsy Children's Health Intelligence Through the Rori Algorithm Approach - Nilawati Tadjuddin; Deri Firmansah; Shoffi Maulia Sari; Nahlaaisyah Nahlaaisyah (FOUNDAE (Foundation of Advanced Education), 2025)
This study examines the implementation of the RORI Algorithm (Responsive–Observative–Reflective–Integrative), a four-stage therapeutic approach designed to help caregivers identify the needs of children with Cerebral Palsy (CP) and develop applicable home-based interventions. The research aimed to explore its application in educational services for children with CP in Lampung, Indonesia, and to assess its contribution in addressing the shortage of educators and promoting equitable access to inclusive education. The study was conducted from June to September 2024 in Bandar Lampung, South Lampung, and Pesawaran, with the main activities centered at Arrusydah II Kindergarten. Participants included children with CP, parents, teachers, and caregivers from the CP community, selected purposively and verified through observation. Findings indicate that the RORI Algorithm effectively stimulates cognitive functions, strengthens motor coordination, and enhances children’s participation in therapy and inclusive learning activities. The method offers adaptive interventions that support caregivers and reinforce inclusive education. The RORI Algorithm holds potential for broader application as a holistic approach to improving the quality of life for children with CP, with recommendations for further large-scale research.